CONTRASTING MINERAL ASSOCIATIONS BETWEEN TWO WOLLASTONITE-BEARING CALC-SILICATE GNEISSES, EASTERN SØR RONDANE MOUNTAINS, ANTARCTICA - ASAMI, Masao; GREW, Edward S.; MAKIMOTO, Hiroshi (National Institute of Polar Research, 1993)
P(論文) Calc-silicate gneisses are found at Austhamaren and Eremitten in the polymetamorphic granulite-and amphibolite-facies metamorphic rocks of the eastern Sør Rondane Mountains. The diagnostic assemblage in the Austhamaren calc-silicate is garnet (Grt)-quartz (Qtz)-wollastonite (Wo)-calcite (Cal), whereas Wo-plagioclase (Pl)-scapolite (Scp)-Qtz and Wo-Cal-Scp-Qtz are characteristic assemblages in the Eremitten gneiss. Wollastonite and calcite are nearly end member CaSiO_3 and CaCO_3. The other major phases approach the calcic end members : garnet is 80-91mole% grossular, plagioclase is An_<88-94>, and scapolite 77-83mole% meionite. Clinopyroxene is hedenbergite (Fe/(Fe+Mg)=0.50-0.67). The reactions Grt+Qtz=Wo+An and Grt+CO_2=Wo+Scp+Cal relate the assemblages in the Austhamaren and Eremitten samples. The two assemblages could be interepreted to result from a regional pressure decrease from Austhamaren in the north to Eremitten in the south. An alternative interpretation is that the Eremitten Wo-Scp assemblages formed at somewhat higher CO_2 activities, and Wo-An, at a slightly higher bulk Na/Ca ratio, compared to the Austhamaren assemblage. X_<CO_2>/(CO_2+H_2O) in the associated fluid phase) is estimated to have been buffered at <0.3 in the Eremitten rock and at 0.1-0.2 in the Austhamaren rock (for T=760-800℃, P=7-8kbar). X_<CO_2> remained low during a nearisobaric temperature decrease to T≤600℃ following peak conditions at Eremitten when garnet selvages developed around wollastonite, scapolite, and plagioclase and scapolite was partially replaced by Pl+Cal+K-feldspar symplectite. departmental bulletin paper